Keamanan Kemasyarakatan Dalam Pembangunan Kawasan Perbatasan Indonesia-Malaysia di Kalimantan Utara - Sonny Sudiar Sudiar; Andi Purnawarman Purnawarman (Jurnal Paradigma (JP), 2022)
This study aims to explore the societal security as a new approach of country’s border area development policy. The concept of societal security is becoming an important topic when it relates to the development of border area. Indonesia shares the borderline with Malaysia in North Kalimantan Province. However, the condition of residents in that area is marked with severe underdevelopment. Responding to the issue, Indonesian border development policy began to adopt simultaneously economic approach and environmental approach besides the traditional security approach which emphasizing military presence in the border area in order to boost the economy and increase the prosperity of the border area residents. This study is a field research (conducted at Krayan, Indonesia and Ba’kelalan, Malaysia) and qualitative approach was applied. Data obtained through participant observation and in-depth interview to several informants. Data was analyzed using descriptive method with emphasizing in data segmentation process. The result suggest that Indonesian government needs to include the societal security approach in the policy as the people who live in the border area have their unique customs and traditions (as their identity) that could be at odds with current policy. In addition, it was noticed that the adoption of societal security approach will complete the picture of North Kalimantan border area policy and could go hand in hand with other approaches as a country’s border area development program.